The Syntactical Interference of Indonesian Language by Indonesian in Speaking English - Bahar, Pratiwi; Aras, Muhammad Sahrir (AhInstitute of Research and Community Service (LP2M) Institute of Social Sciences and Business Andi Sapada, 2023)
Sociolinguistics is a discipline that focuses on the study of linguistic variation. It claims that in multilingual culture where some languages coexist in a society, they affect each other, such as in Indonesia. Thus, Interlanguage could happen in this area. A person who is bilingual or multilingual,/usually finds a problem in speech as an effect of language contact. This phenomenon is called interference. This study aims to elaborate on the kinds of syntactical interference and to describe the most frequent syntactical interference made by the elite group of Indonesia in speaking English. Another purpose of this research is to disclose the factors that make the elite group of Indonesia do those kinds of syntactical interference in speaking English. The researcher collected the primary data from 20 respondents of the Indonesian elite group by conducting interviews and recordings. The analysis was conducted by using descriptive quantitative and qualitative methods. The results show that the elite group of Indonesia makes several kinds of syntactical interference, including omission, addition, misformation, and misordering. This is caused by the unawareness in the effort to transfer the original structure of the Indonesian language into English. This research has significance as follows: (1)Theoretical benefit: this research, will show the most frequent syntactical interference produced by Indonesians in speaking English. (2) Practical benefit: It will give the readers insights and awareness about the various kinds of interference, especially in syntactical interference that usually emerges in English production.